Quality of Elementary School Trial Tests on Indonesia Language Subjects in Term of Material, Contruction, and Language Aspects - Sulis Setiawati; Merry Lapasau (Universitas Indraprasta PGRI, 2021)
The achievement of the learning process results can be measured by the teacher by using the test as one of the benchmarks. The test is given by the teacher to students as one of the evaluation tools, in accordance with basic competencies and also indicators of achievement of learning outcomes. Thus, the teacher must really ensure that the questions or tests being tested are of high quality and can map the actual abilities of students. The purpose of this paper is to identify and describe the quality of school exam questions in Indonesian subjects in terms of material, construction, and language aspects. The data used is in the form of a package of test questions (try out) for the elementary school level exams in 2020. The research method used in this research is descriptive qualitative with content analysis techniques. Based on the results of the analysis, it can be concluded that the quality of the 2019/2020 elementary school test test questions in Indonesian subjects in terms of material, construction, and language aspects still needs to be improved, especially in the language and material aspects. The language aspect in question includes spelling, punctuation, and letter writing. The language aspect in question includes spelling, punctuation, and letter writing. Then on the material aspect in terms of the suitability of each item with the indicator.Keywords: Kualitas Soal, Bahasa Indonesia.